The Village Secretary's Strategy for Coordinating Village Officials in Conducting Village Deliberations - Mohamad Yusup; Nazmudin Nazmudin; Ujang Saepudin (HK-Publishing, 2024)
Abstract The core issue of this study concerns the role of the Village Secretary—a village official whose duties include coordinating all village officials during the village deliberation process. The research question addresses the strategies employed by the Village Secretary to coordinate village officials in organizing village deliberations in Umbulan Village, Cikeusik District, Pandeglang Regency, while also examining the influencing factors. To address this research question, a qualitative research method with a descriptive approach was selected. Data collection involved structured interviews and participatory observation to obtain primary data, alongside documentation techniques for secondary data. Informants were selected using purposive sampling, specifically the